Preparation of graphene nanowalls on nickel foam as supercapacitor electrodes. (1st June 2018) - Zhou, Haitao; Liu, Dabo; Luo, Fei; Luo, Bingwei; Tian, Ye; Chen, Dongsheng; Shen, Chengmin
Abstract : Graphene nanowalls (GNWs) were deposited on the surface of the copper foil, nickel foam and glass using the plasma‐enhanced chemical vapour deposition (13.56 MHz) method. The etching effect of hydrogen on the morphology of the GNWs was investigated by varying the CH4 /H2 ratio during the graphene growth. Supercapacitor electrodes made of GNWs on nickel foam were tested with cyclic voltammetry and galvanostatic charge/discharge methods, showing premium electrical double‐layer performance and cyclic stability.